A survey of motion planning techniques for humanoid robots. (16th November 2020) - Tazaki, Y.; Murooka, M.
Abstract : This paper provides a brief survey of motion planning techniques for humanoid robots. Among various related topics that constitute the broad framework of motion planning of humanoid robots, this paper covers two actively researched topics, namely, bipedal locomotion planning based on low dimensional dynamical models and multi-contact problems that involve non-coplanar and non-scheduled contact. For each of these two classes of planning problems, after reviewing the theoretical background and commonly used problem formulation, existing planning methods are classified based on their concepts and their respective advantages and shortcomings are discussed.